KORELASI FENOMENA URBAN HEAT ISLAND DAN IMPLIKASINYA TERHADAP KETEPATAN PENENTUAN AWAL BULAN KAMARIAH DALAM ILMU FALAK - Nurjihan; Chotban , Sippah (HISABUNA: Jurnal Ilmu Falak, 2025)
The rapid development of urbanization in the era of globalization has created complex phenomena that not only affect the socio-economic aspects of society but also significantly impact the climatological and atmospheric conditions of urban areas. This phenomenon has become a serious concern in urban climatology studies due to its multidimensional effects, which are not limited to thermal comfort and energy consumption, but also potentially influence various human activities that depend on stable atmospheric conditions. This research raises two main questions, how does the urban heat island (UHI) phenomenon occur and what are its implications for weather in urban areas? and what is the correlation between UHI and the accuracy of determining the beginning of the lunar month (hilal) in Islamic astronomy (Ilmu Falak)? This study employs a qualitative, library-based research method using both syar’i (Islamic jurisprudential) and scientific approaches to explore the collaboration between astronomical concepts and the foundational principles of Ilmu Falak. Data were collected through library research by quoting, adapting, and analyzing relevant literature using content analysis. The findings were then reviewed and concluded. The results of the study indicate that the UHI phenomenon is caused by the reduction of green open spaces and the increase in urban activities, leading to temperature rise, atmospheric turbulence, and the formation of pollutant haze. These conditions reduce night sky clarity and interfere with hilal visibility due to diminished light contrast. The implications of this research enrich falakiah studies on the correlation between UHI and hilal observation (rukyatul hilal) and highlight the need for mitigation strategies by Islamic calendar-setting institutions to improve the accuracy of hilal observation and the timeliness of Islamic worship.